Pengaruh Debt to Equity Ratio Dan Return On Assets Ratio Terhadap Audit Delay: Studi Kasus Pada Perusahaan Sektor Barang Konsumen Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2021 - Delviana Maiherawati; Indah Damayanti; Adam Ramdani; Robbi Saepul Rahman (Acman: Accounting and Management Journal, 2022)
Researchers conducted research intending to know the effect of the Debt to Equity Ratio and Return on Asset Ratio on Audit Delay in consumer goods sector companies listed on the Indonesia Stock Exchange in 2016-2021. Moreover, this research analyzes the factor that has the most dominant influence between the Debt to Equity Ratio and Return Asset Ratio to Audit Delay in consumer goods sector companies listed on the Indonesia Stock Exchange in 2016-2021. The objects of research are as many as nine companies as gross as consumers listed on the Indonesia Stock Exchange. Based on research using multiple linear analyses shows that if the Debt to Equity Ratio and Return on Assets ratio increase, audit delay will increase. Every decrease in the Debt to Equity Ratio of 1% will increase audit delay. Likewise, every decrease in the Return on Assets Ratio of 1% will increase audit delay. To increase Debt to Equity, the company should pay attention to matters relating to the Debt to Equity Ratio, such as debt and equity in the company concerned. To minimize audit delay, the auditor should pay more attention to matters related to Return on Assets such as profits and assets in the company concerned. To minimize audit delay, the auditor should pay more attention to related matters that can affect the results of the company's financial ratios, especially the Debt to Equity Ratio and the Return on Assets ratio.